A Forkhead Box Protein C2 Inhibitor: Targeting Epithelial–Mesenchymal Transition and Cancer Metastasis. (30th May 2018) - Castaneda, Maria; Chen, Luxi; Pradhan, Lagnajeet; Li, Shichang; Zein, Ruba; Lee, Yeongju; Lim, Hyun‐Suk; Nam, Hyun‐Joo; Lee, Jiyong
Abstract: The epithelial–mesenchymal transition (EMT) has been suggested as a new target for therapeutic intervention of metastatic cancer. Forkhead box protein C2 (FOXC2) is known to be necessary for initiating and maintaining EMT, and therefore bestows on cancer cells metastatic and cancer stem cell (CSC)‐like phenotypes, allowing cells to acquire higher motility, invasiveness, self‐renewal, and therapy resistance. Here, we describe the first inhibitor of FOXC2, MC‐1‐F2. MC‐1‐F2 was able to induce cadherin switching and reverse EMT through the degradation of FOXC2 and blocking of its nuclear localization. In addition, MC‐1‐F2 was very effective in inhibiting cancer cell migration and invasion. As the first small‐molecule inhibitor of FOXC2 and the first compound targeting EMT‐associated transcription factor, MC‐1‐F2 will pave the way for a new anticancer therapeutic agent targeting metastatic cancer and help to elucidate the network of EMT signaling pathways. Abstract : First in the class : The epithelial–mesenchymal transition (EMT) is a potential new target for therapeutic intervention for metastatic cancer. Forkhead box protein C2 (FOXC2) plays a pivotal role in initiating and maintaining EMT. A small‐molecule FOXC2 inhibitor, MC‐1‐F2, was found to induce cadherin switching and reversal of EMT progression, leading to inhibition of cancer metastasis in vitro.